Cruising for Plants and Progress: Marian and David Fairchild and the Allison V. Armour Expeditions, 1925-1933 - Latham, Janet Mosely (East Carolina University, 2019)
This thesis examines the Allison V. Armour Expeditions that took place between 1925 and 1933 aboard research vessel Utowana. Led by American botanist David G. Fairchild and sponsored by philanthropist Allison V. Armour, they spanned the Atlantic World and beyond, visiting over fifty countries and European colonies to collect plant material and foodways for introduction into the U.S. These expeditions occurred during an era of extensive and intensive neocolonial scientific investigations led by the global north into the tropical regions of the world. David Fairchild's contributions to American agriculture and cuisine are well known, but the collaborative scientific relationships he shared with his wife, Marian Bell Fairchild, and their patron and friend, Allison V. Armour, that were essential to David's success, are not known. Marian and Armour shared David Fairchild's desire to make America more cosmopolitan through the introduction of foreign food plants and foodways. They travelled the world to collect plants to diversify American agriculture as well as to share scientific agricultural techniques with the places they visited. They believed in cultural exchange not economic exploitation. Examining documents and images created during the Armour/Fairchild Expeditions through the historical perspectives of neocolonialism, cosmopolitanism, and gender illustrates the Fairchild's and Armour's expedition experiences in the tropical regions. These experiences influenced them positively and, in turn, they brought their knowledge of the exotic home in order to influence U.S. culture. The Fairchilds and Armour approached international plant and knowledge collection in a positive cosmopolitan manner thereby mitigating their neocolonial impact on the regions they visited. They believed in the mutual exchange of plants and culture with the peoples they met whom they treated as individuals and not a primitive "other." The Fairchilds were a collaborative scientific couple whose positive cosmopolitanism, views of gender, and humanitarian outlook, shared by Allison Armour, positively influenced the neocolonial nature of the Armour/Fairchild Expeditions.
Keywords: Atlantic World; Utowana; Scientific expeditions; Fairchild, David, 1869-1954; Fairchild, Marian, 1880-1962; Botanists; Food habits